2016
DOI: 10.4238/gmr.15027735
|View full text |Cite
|
Sign up to set email alerts
|

SNP at miR-483-5p-binding site in the 3'-untranslated region of the BSG gene is associated with susceptibility to esophageal cancer in a Chinese population

et al.

Abstract: ABSTRACT. The aim of this study was to investigate the association between a functional variant of the basigin (BSG) gene, caused by a polymorphism (rs11473) at the miR-483-5p binding site, and the risk of esophageal squamous cell carcinoma (ESCC) in the Chinese population. The rs11473 polymorphism was genotyped in 624 esophageal cancer patients and 636 cancer-free age-and gendermatched controls using polymerase chain reaction restriction and direct sequencing. The functional variants resulting from the BSG rs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…MiR-483-5p is also involved in a variety of disease processes, such as facilitating infected lymphocytes through the blood-brain barrier, polycystic ovary syndrome, and liver fibrosis (Shen et al, 2013 ; Li et al, 2014 ; Chen et al, 2015 ; Shi et al, 2015 ; Curis et al, 2016 ), and it also plays an important role in the development of many tumors such as esophageal, oral squamous cancer, and lung adenocarcinoma (Song et al, 2014 ; Li et al, 2016 ; Xu et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…MiR-483-5p is also involved in a variety of disease processes, such as facilitating infected lymphocytes through the blood-brain barrier, polycystic ovary syndrome, and liver fibrosis (Shen et al, 2013 ; Li et al, 2014 ; Chen et al, 2015 ; Shi et al, 2015 ; Curis et al, 2016 ), and it also plays an important role in the development of many tumors such as esophageal, oral squamous cancer, and lung adenocarcinoma (Song et al, 2014 ; Li et al, 2016 ; Xu et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a multifunctional highly glycosylated integral transmembrane protein, Basigin (BSG/CD147) has been shown that acts as a key modulator in the pathogenesis of cancer invasion and metastasis. Li et al found that the miR-483-5p binding site polymorphism in the 3'-UTR of the BSG gene is related to increased susceptibility of esophageal cancer, and the miR-483-5p/BSG axis may play an important role in esophageal cancer carcinogenesis 2 . In pancreatic cancer, DPC4/Smad4 has been identified as a tumor-suppressor gene and is regarded as a target of miR-483-3p, and the miR-483-3p over-expression not only inhibits DPC4/Smad4 protein level, but also represses the expression of DPC4/Smad4 downstream targets like PAI, p21 and Msx2 19 .…”
Section: The Pathways and Interactions Of Mir-483 Involved In Digestimentioning
confidence: 99%
“…Digestive tract cancers (DTCs) is the most common malignant tumors in the world, and it is a multifactorial and heterogenous disease whose beginning and development can be ascribed to the accumulative effect of genetic predispositions, environment factors, and their complicated interplay 1 . Despite the considerable advances in surgery and medical technology in recent times, DTC remains a critical concern with high morbidity and mortality, as it is diagnosed mainly at late stages 2 . Since a class of small noncoding RNAs termed microRNAs were recognized several years ago, numerous investigators have probed into the relationship between the specific miRNAs dysregulated expression levels and the diseases phenotypic changes 3 .…”
Section: Introductionmentioning
confidence: 99%
“…BSG rs11473 polymorphism within miR-483-5p binding site was reported to be associated with increased risk of esophageal cancer in a Chinese population [29]. Other studies failed to demonstrate an association between BSG polymorphisms and risk of schizophrenia [30], cerebral malaria [31], and atherosclerotic cerebral infarction [32].…”
Section: Discussionmentioning
confidence: 99%